Desenvolvimento de dispositivo para imobilização pélvica e efeitos da fotobiomodulação (830 nm) no tecido muscular em diferentes condições experimentais : estudo em ratos - Arruda, Eder João de (Universidade Federal de São Carlos, 2017)
The effects of photobiomodulation by low level laser therapy (LLLT) on muscle tissue are well known. However, it is not found in the literature studies about the application of LLLT in the pelvic musculature under experimental disuse. The present thesis focused its analysis on three aspects: point out the anesthetic option which interferes the least in the metabolism of glucose, considering that muscle tissue is one of the main sites involved in glycemic regulation (study I), thus the results from this study could support the development of an non invasive pelvic immobilization model in rats (study II) and evaluate its effectiveness, through the chemo-metabolic response of the involved musculature before the muscular atrophy. Then we sought to evaluate if there is reversal of this muscle conditions (study III) by applying LLLT during and after the pelvic immobilization period. The three studies were performed with 80 male rats divided into different experimental groups. For the statistical evaluation, in study I the data were submitted to the Shapiro-Wilk normality test, followed by the ANOVA and Tukey test. In studies II and III the data were submitted to the Kolmogorov-Smirnov normality test followed by ANOVA and Tukey's test (a critical level of p <0.05 was stablished). In study we used 32 Wistar rats (n = 4), aged between 3 and 4 months, weighing 250±50g, distributed in eight groups, of which 4 groups were submitted to the glucose tolerance test (GTT) and another 4 submitted to the insulin tolerance test (ITT). We compared four anesthetics: Thiopental sodium (T, 40 mg/kg), Zolazepan (Z, 50 mg/kg), Ketamine-Xylazine (K, 35 mg/kg and 4 mg/kg) and Tribromoethanol (TRI, 250mg/kg). We concluded that Thiopental and Tribromoethanol anesthetics are the safest because they do not interfere in the glycemic control dynamics. In the study II, we distributed 18 rats were in three groups (n = 6): control (C), pelvic immobilization for 7 days (PI) and remobilized for 7 days after 7 days of device use (RP7). We found a difference (p <0.05) between groups: pelvic muscle glycogen reserves were reduced by 68% in the PI group and 50% in the RP7 group. The group PI had a delay of 10% in the glucose decay constant (KITT). Considering the total protein/DNA ratio groups PI and RP7 presented a reduction of 28% and 24% in the gluteus maximus and 32% and 16% in the iliopsoas, respectively. In the evaluation of the serum concentration of interleukin 6, the group PI had an increase of 27.3% and RP7 19.2% compared to the C. Interleukin 10 increased 30.4% and 14.9% in the IP and RP7 groups, respectively. Tumor necrosis factor (TNF-α) presented a discrete but significant increase of 5% only in the PI group compared to group C. Therefore, the experimental model proved to be effective in mimicking the deleterious effects of disuse, and this effects were not recovered after removing the immobilization device. Based on this findings, study III used 30 rats distributed in five groups (n=6), being; Control (C), Pelvic Immobilization (PI), Immobilized 7 days and remobilized for 7 days (IR), Laser during pelvic immobilization (LDPI) and Laser after pelvic immobilization (LAPI). Thus, the LLLT (Ga-Al-As, continuous λ = 830 nm, P = 30 mW, beam area = 0.116cm², T = 14s, fluency of 3,62J/cm², E = 0.42J; power density = 0.26mW/cm²) was applied on 8 points for 7 consecutive days. This study showed that, considering pelvic immobilization in the experimental condition, LLLT can minimize the catabolism by promoting an increase of glycogen reserves in the involved muscles, improving the total protein/DNA ratio, reducing pro-inflamatory activity (IL-6 and TNF- α) and increasing the anti-inflammatory activity (IL-10), especially when the LLLT was applied during the period of immobilization, providing that skeletal muscles maintain better metabolic and structural conditions even under disuse conditions. Finally, this work was successful in elucidating thiopental and tribromoethanol anesthetics as the ones that least interfere with glucose metabolism, so that this favored the development of an experimental model of disuse with marked muscular catabolism, which can be attenuated by means of photobiomodulation (830 nm).
Development of devices for pelvic immobilization and photobiomodulation effects (830 nm) in muscle tissue under different experimental conditions : study in rats
Keywords: Músculo; Imobilização pélvica; Anestesia; Fotobiomodulação; Ratos; Muscle; Pelvic immobilization; Anesthesia; Photobiomodulation; Laser; Rats; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL